Genetic polymorphisms and metabolism of endocrine disruptors in cancer susceptibility Polimorfismos genéticos e metabolismo dos desreguladores endócrinos na suscetibilidade ao câncer - Ana Hatagima (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Epidemiological studies have estimated that approximately 80% of all cancers are related to environmental factors. Individual cancer susceptibility can be the result of several host factors, including differences in metabolism, DNA repair, altered expression of tumor suppressor genes and proto-oncogenes, and nutritional status. Xenobiotic metabolism is the principal mechanism for maintaining homeostasis during the body's exposure to xenobiotics. The balance of xenobiotic absorption and elimination rates in metabolism can be important in the prevention of DNA damage by chemical carcinogens. Thus the ability to metabolize and eliminate xenobiotics can be considered one of the body's first protective mechanisms. Variability in individual metabolism has been related to the enzymatic polymorphisms involved in activation and detoxification of chemical carcinogens. This paper is a contemporary literature review on genetic polymorphisms involved in the metabolism of endocrine disruptors potentially related to cancer development. Estudos epidemiológicos estimam que cerca de 80% dos cânceres estão relacionados a fatores ambientais. A suscetibilidade individual ao câncer pode resultar de vários fatores relacionados ao metabolismo de xenobióticos, reparo do DNA, expressão de genes supressores de tumor e protoncogenes e estado nutricional. O metabolismo é o principal mecanismo para manter a homeostasia durante a exposição dos organismos aos xenobióticos. O equilíbrio das taxas de absorção e eliminação dos xenobióticos tem um papel importante na prevenção de danos no DNA, provocados por carcinógenos químicos. Sendo assim, a habilidade de metabolizar e eliminar os xenobióticos pode ser considerada uma das primeiras linhas de defesa dos organismos. Variações no metabolismo individual têm sido relacionadas aos polimorfismos enzimáticos, envolvidos na ativação e desintoxicação de carcinógenos químicos. Neste trabalho, é realizada uma revisão da literatura contemporânea sobre os polimorfismos genéticos envolvidos no metabolismo de desreguladores endócrinos, potencialmente associados ao desenvolvimento do câncer.